If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = 5x Reorder the terms: 2 + 4x = 5x Solving 2 + 4x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + 4x + -5x = 5x + -5x Combine like terms: 4x + -5x = -1x 2 + -1x = 5x + -5x Combine like terms: 5x + -5x = 0 2 + -1x = 0 Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| a+23=31 | | 2x+9=6x+51 | | x^4-20x+64=0 | | x^2+6x-1=0 | | 12x-8=136 | | 2x(3.7-9.1)= | | 17h-47+6h=160 | | 1.2m=-0.72 | | n+4.7=12.2 | | 75w^2-48=0 | | 14+4k=2k-11 | | ax-ay+bx-by= | | 3(x^2+4)+4=52 | | y-5.6=-7.2 | | -8=27+t | | (8x^2-18)(x^2-9x+8)=0 | | (8x^2-18)(x^2-9x+8)=y | | 10x^2-13x-3=0 | | 12x^3-6x^2-2x+1= | | 15x+8y=165 | | 27a-11=-25+23a | | 27a+11=-25+23a | | 4-2u=3-3u | | y-5.6=7.2 | | y=4(3)-3 | | 11z+3-4z=5z | | y=4(1)-3 | | 3(3p+5)=3p | | y=4(-1)-3 | | -4g+12=g+2 | | x+x+2+x+4=189 | | -10g+48=4g |